242 "I Want to Break Free": Harming Older Patients Through Restraint, Isolation and Tethering. (16th September 2019) - Heywood, Sarah; Fitzpatrick, Donal; Doyle, Kate; Finn, Ger; Gallagher, Paul
Abstract: Background: The older inpatient population is a particularly frail cohort with high rates of delirium, falls and immobility. These patients require skilled gerontological nursing with high levels of supervision. Despite this, restraints such as bed rails continue to be common. Tethering through intravenous drips and urinary catheters are another form of restraint. Methods: We performed a chart review and a bedside observation of patients aged ≥75 on medical wards admitted for ≥72 hours. We excluded patients who were critically unwell or imminently dying. We used the open source software package PSPP to complete the statistical analysis. Results: We reviewed 100 patients, of whom 25 were restrained in some way (most commonly by bed rails 80%), 10 were tethered (through intravenous drips, oxygen tubing, urinary catheters and others), 7 were in isolation for infection control reasons. Restraint was associated with greater dependence in mobility and function, reduced time out of bed (Mann Whitney, P< 0.05), delirium and incontinence (chi square, p <0.05). Isolation was associated with greater physical dependence (Mann Whitney, P< 0.05), and tethering was associated with incontinence (chi square, p <0.05). The relatively low number of isolated and tethered patients reduced the power of the study. 50% of patients with a urinary catheter did not have a clear indication and only 14% of catheterised patients had leg bags Conclusion: Patients who are restrained are clearly frailer, more dependent, spend more time in bed, have higher rates of delirium and incontinence. These are particularly vulnerable patients who need high levels of attention from both medical and nursing staff. Supervision is always superior to restraint but requires investment in staff and resources. Patients who are isolated are also more physically dependent. Tethering should be minimised. Simple measures such as leg bags are underused.